A Matter of Principle(s) ? Acquiescence in International Humanitarian Law - Robert Kolb; Hêche, Aymeric (My University, 2026)
The purpose of this post is to examine the relevance of general principles of law, particularly through the example of acquiescence. More particularly, the application of general principles external to IHL in IHL is rarely discussed. This post begins with an overview of general principles of law, outlines the fundamental elements of acquiescence, lists several cases of applications, and identifies some other such “external” general principles of law that may be relevant to IHL.